[RETRACTED] Application of Bamboo Radial Compression Joint for Tension and Knock-Down Structures - Andry Widyowijatnoko; Rakhmat Fitranto Aditra (Universitas Pendidikan Indonesia, 2018)
==========================================================Available online: 09 April 2018 This article has been retracted by Indonesian Journal of Science and Technology Editorial team, following clear correspondence and confirmation with authors. The paper is retracted from 30 May 2021.==========================================================Bamboo applications become popular recently by the community due to the rise of environmental awareness, including for post-disaster building. Two aspects of post-disaster buildings were considered: i.e. its performance and its recyclability. This research explore ability of bamboo as tensile structure, and also as knock-down structure. Bamboo radial compression (barcom) connection was explored by these aspects. Barcom joint is one of the solutions to be effectively used for gaining the tensile strength of bamboo by converting tensile load parallel to fiber into radial compression perpendicular to fiber. Barcom joint was tested to acquire its load capacity and its future improvement. The load test showed that the barcom connection could reach up to 21.61 kN. To improve this capacity, either better wire or special washer design could be proposed. The adaption in previous built structure (i.e. Three Mountain Building in Serangan island, Bali and knock-down bamboo geodesic dome in Colombia) was used as a case-study. In the construction of Three Mountain Building, barcom joint was used to hang the bamboo rafters and acts as tension-like member. Meanwhile, the use of barcom joint in Colombia was intended to connect the bamboo with the steel bowl connector which could be dismantled and reused again many times.